2020
DOI: 10.3390/ijerph17124406
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Sailing Experience to Reduce Psychological Distress and Improve the Quality of Life of Breast Cancer Survivors: A Survey-Based Pilot Study

Abstract: Background: Growing evidence indicates that physical/sporting activities may improve the health outcomes and quality of life (QoL) of breast cancer (BC) survivors. Since recent reports have suggested that sailing can improve the psychophysical well-being and QoL of people with disabilities, this pilot study evaluated the effectiveness of a tailored sailing experience on the QoL and psychological distress (PD) of BC survivors. Methods: A group of 19 breast cancer survivors, who were attending the Cancer Rehabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Cancer survival improvements during the past few decades have resulted in a large and growing population of long-term BC survivors [ 2 , 15 ]. Hence, it is of primary importance to improve the health-related QoL of this population [ 3 , 5 , 6 , 11 , 15 , 16 , 17 ]. Of note, significant concerns exist regarding chronic upper extremity dysfunction as a long-term complication that can occur after BC treatments [ 3 , 4 , 5 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer survival improvements during the past few decades have resulted in a large and growing population of long-term BC survivors [ 2 , 15 ]. Hence, it is of primary importance to improve the health-related QoL of this population [ 3 , 5 , 6 , 11 , 15 , 16 , 17 ]. Of note, significant concerns exist regarding chronic upper extremity dysfunction as a long-term complication that can occur after BC treatments [ 3 , 4 , 5 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic aspiration may increase the incidence of surgical site infection, clinic visit, and mental stress of patients [8]. While recent research supports that physical activity (PA) interventions can improve physical functioning, treatment-related symptoms, and QoL in cancer survivors [3,5,10,11], the possible effectiveness of PA in cases developing seroma has yet to be demonstrated [12]. Therefore, we herein evaluated for the first time the possible effects of a structured PA pathway for upper extremity recovery and QoL improvement in a case of peri-prosthetic seroma after BC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The results show a reduction in the level of anxiety and distress and an improvement in the quality of life in the study group. As part of the intervention, in addition to sailing theory and practice, the patients had sessions with a psychologist and a physical exercise specialist [ 22 ]. In Poland, since 2015 (with a break during 2020 because of the SARS-CoV-2 pandemic), annual sea cruises for cancer patients—Onco-Cruises (Polish: Onko-Rejs)—have been organized by the Onco-Cruise-I Choose Life Foundation.…”
Section: Introductionmentioning
confidence: 99%
“…According to the 2007 qualitative study by Sabiston and colleagues in breast cancer survivors [10], experiences as members of dragon boat teams provided "opportunities to (re)gain a sense of personal control, develop new identities as athletes, and overcome physical challenges." Accordingly, evidence from other survey-based qualitative studies and the only available narrative review on the topic revealed significant benefit on psychological distress and quality of life following water sports such as sailing, kayaking and dragon boat in cancer survivors [10][11][12]. The choice of a natural environment such as a blue/green gym may represent an added value and an enjoyable alternative to the conventional forms of indoor exercise.…”
Section: Introductionmentioning
confidence: 99%